1985
DOI: 10.1021/jf00064a025
|View full text |Cite
|
Sign up to set email alerts
|

Racemization kinetics of amino acid residues in alkali-treated soybean protein

Abstract: Exposing soy proteins to alkaline conditions (pH 8-14), for various time periods (10-480 min) and temperatures (25-95 °C at 10 °C intervals), induced increasing racemization of L-amino acid residues to D isomers. Relative susceptibilities of most amino acids were correlated with a linear free energy relationship based on plots of the ratio of the logarithm of the rate of racemization of any amino acid to that of alanine vs. *, a parameter that measures electron-donating inductive effects of amino acid side ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 8 publications
5
61
1
Order By: Relevance
“…After prolonged or severe heat treatments, a degree of racemization rate was reported (Liardonn and Hurrell, 1983;Bada, 1984;Friedman and Liardon, 1985;Luzzana et al 1999). In our results, the prolonged heat treatment (115°C, 180 min) revealed a D-Asp content of 28.1%, that reasonably agree with previously reported D-Asp racemization rates on heated (121°C) chicken muscle protein, 22.4% and 26.3%, after 4 h and 8 h, respectively (Liardon and Hurrell, 1983).…”
Section: Resultssupporting
confidence: 92%
“…After prolonged or severe heat treatments, a degree of racemization rate was reported (Liardonn and Hurrell, 1983;Bada, 1984;Friedman and Liardon, 1985;Luzzana et al 1999). In our results, the prolonged heat treatment (115°C, 180 min) revealed a D-Asp content of 28.1%, that reasonably agree with previously reported D-Asp racemization rates on heated (121°C) chicken muscle protein, 22.4% and 26.3%, after 4 h and 8 h, respectively (Liardon and Hurrell, 1983).…”
Section: Resultssupporting
confidence: 92%
“…Whether or not other D-amino acids are derived from yeasts is still open to discussion. Previous studies indicated that heat treatment contributed to significant racemization in bread and soybean protein and that racemization was not obtained in hamburgers [14,16]. In the present study, the ratio of D-pipecolic acid in tofu, made from soybeans, beef, bovine liver and bread, did not increase after heat treatment.…”
Section: Discussioncontrasting
confidence: 61%
“…In other words, food proteins are treated with heat or alkali conditions before consumption. Some studies have reported that heat, alkali or the combination of both treatments caused amino acid racemization in food proteins [14][15][16]. Therefore, D-amino acids may be detected in human physiological fluids, since the above-mentioned natural and processed foods are typical of the modern diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relationship between racemization rates (k) relative to Ala, and the inductive constant (s*) of the amino acid side chain R in RCH(NH 2 )COOH. Adapted from [199] and [93].…”
Section: 4mentioning
confidence: 99%